Assessment of the water quality parameters in relation to fish community of Osinmo reservoir, Ejigbo, Osun State, Nigeria - KOMOLAFE, O.O; ADEDEJI, A.A; FADAIRO, B (2023)
Physicochemical indices of water body changed seasonally and this necessitated an investigation to assess the water quality parameters of Osinmo reservoir in relation to its fish species. The water quality parameters were measured using standard methods. Results obtained show that the reservoir is alkaline in nature with dissolved oxygen concentration (1.8-7.2 mgl-1) and alkalinity (64 CaCO3 mgl-1-108 CaCO3 mgl-1) which were within the optimum range for growth and survival of fish. Four families of fish comprising eight species were encountered. The sex-ratio of five species which were statistically different (P<0.05) indicated reproductive efficiency populations while other fish species whose sex-ratio differed insignificantly (P>0.05) revealed a growing population. The well-being of the fish species was adequate as observed in the least mean condition factor of 0.666±0.057 in C. gariepinus and the highest mean of 2.000±0.242 in S. galilaeus. The productivity of the reservoir can be improved through proper management of the water body